Personality Traits of Moira in Nora Robert’s Valley of Silence Novel - Hidayah, Radhiyatus Sara; Arbi, Anggun Purnomo (English Language and Literature in Education Journal, 2024)
This research delves into the critical role of character development in narratives, specifically focusing on Nora Roberts’ novel “Valley of Silence” (2006) and the characterization of its main protagonist, Moira. The study aims to meticulously analyze Moira’s personality traits, drawing upon McCrae and Costa’s comprehensive personality trait theory (2003), which encompasses dimensions such as extraversion, neuroticism, openness, conscientiousness, and agreeableness. Furthermore, it employs Shlomith Reymon Kennan's characterization theories (2005) to explore the methods utilized in portraying Moira’s traits effectively within the narrative framework. Employing a descriptive qualitative method, data were meticulously extracted from the novel's script, allowing for a detailed examination of Moira’s characterization through the lens of indirect presentation and speech patterns. The findings reveal Moira’s predominant personality trait as extraversion, supported by consistent behavioral manifestations aligned with this trait, albeit tempered by contextual influences. This nuanced understanding highlights the intricacies of character depiction in literature and underscores the importance of employing triangulation techniques for robust data validation in future studies. This study contributes valuable insights for educators and literary analysts, providing a deeper understanding of character dynamics and suggesting pedagogical enhancements in literature studies. By elucidating Moira’s multifaceted personality traits and the narrative techniques employed, this research enriches scholarly discourse on character development and narrative construction in contemporary literature.